Perceptions of Postgraduate Social Work Students in regards to their Undergraduate Field Instruction Supervision Experiences. - Kapfudza, Tafadzwa (My University, 2017)
Social work field instruction is crucial in social work training and it is regarded as a centrally important aspect of social work. It enables the students to practice skills and know the values of the profession that guide their practice. This study focuses on traditional practice of field instruction, commonly referred to as block placement where a student is placed at an agency for a prescribed period in a given year of study to apply theory into practice implementing basic methods of social work; casework, group work and community work, depending on the level of study. The main components of field instruction block placement are the school of social work, the social work student, the agency, the agency supervisor, and the field instruction coordinator. The aim of this research is to explore the perceptions of postgraduate social work students regarding the supervision they received from the agency supervisor on an undergraduate level. The researcher chose exploratory research method to guide this investigation. A sample of eight respondents will be drawn from the population of postgraduate students involved in various programmes in the Department of Social Work at the University of the Witwatersrand during the 2017 academic year. The data will be collected through interviews utilising interview schedule as a data collection tool. Collected data will be interpreted using thematic analysis. It is hoped that insights gained from experiences of students regarding supervision could contribute towards improving the effectiveness of student supervision during field instruction. Recommendations made could assist the university to improve structuring of supervision to optimally meet needs of students in their journey of developing as professionals and preparing them to transit from student supervision to professional supervision in social work. Key words: Social work supervision, student supervision, social work professional supervision, supervisor, supervisee, effective supervision, field instruction,
A Report on a study project to The Department of Social Work School of Human and Community Development Faculty of Humanities University of Witwatersrand In partial fulfilment of the requirements for the Degree Bachelor of Social Work